The Development of Analytical Hierarchy Process (AHP) Model for Optimization of School Operational Assistance (BOS) - Salman Alfarisy Totalia; Trisno Martono; Khresna Bayu Sangka; Winny Swastike; Sigit Wahyudi; Suhadi Suhadi (Budapest International Research and Critics in Linguistics and Education (BirLE) Journal, 2021)
Since its implementation in 2005, the School Operational Assistance (BOS) program has encountered several obstacles. The problems that often arise are the lack of planning and the lack of participation of the school ecosystem, especially in determining plans, planning documents and project priorities. The Analytical Hierarchy Process (AHP) model is a prioritization approach based on the determination of the priority scale on the comparison of one option with another. This approach is widely used to make decisions in various sectors, business, government, management, and education. It is very important to have a solution optimization tool in place to deal with the main problems that arise in allocating these funds. In this research, The AHP model is used to determine the priority scale on the criteria for BOS funds in the current year so that BOS funds can be optimally absorbed and can be utilized properly in its implementation for Vocational High School (SMK) activities. The results showed that the use of AHP made it easier for school residents to prioritize the use of funds for school activities. AHP can also be used for various stakeholders in schools (principals, treasurers, teachers, and committees, parents/guardians) to participate in making decisions about the use of BOS funds to improve school performance and quality.